Endoscope reprocessing: Retrospective analysis of 90,311 samples - Pineau, Lionel (Endoscopy International Open, 2023)
Background and study aims The contamination level of ready-to-use endoscopes published in the literature varies from 0.4 % to 49.0 %. Unfortunately, the comparison and the interpretation of these results are quite impossible, given the limited number of samples and sites included and the differences observed between sampling, culturing methods, and interpretation criteria.Methods The objective of this retrospective study was to analyze the results of 90,311 endoscope samples collected between 2004 and 2021 in 490 private or public hospitals in France.Results Through the full test period, the mean ratio of endoscopes at the action level was 12.6 % (19.5 % including alert level). Of the endoscopy units, 23.0 % had a ratio of compliant endoscopes ≤ 70.0 %. The overall microbial quality of gastroscopes, duodenoscopes, and colonoscopes is improving year by year, whereas an opposite trend is observed for ultrasound endoscopes and bronchoscopes. In 2021, following French guidelines, 13.0 % of the endoscopes should have been quarantined and 8.1 % were at the alert level, meaning that the contamination level of 21.1 % of the endoscopes exceeded what was defined as a maximum acceptable value. Conclusions This study demonstrates that additional efforts, including implementation of microbial surveillance strategies using a standardized sampling method and periodic observational audits, must be made to improve the overall microbiological quality of endoscopes and reduce the risk associated with their use.